Government Policy in Supporting the Expansion of the National Halal Industry into the Global Market - Nanda Alfreda Putri; Honainah, Honainah; Zaenab, Zaenab (Values: Jurnal Kajian Islam Multidisiplin, 2025)
The halal industry has experienced significant growth along with the increasing demand for halal products in the domestic and international markets. This study aims to analyze government policies in supporting the expansion of the national halal industry into the global market. The research method used is a literature study by collecting data from scientific journals, books, and articles from academic databases such as SINTA, Google Scholar, and ResearchGate, which were analyzed descriptively. The results show that government policies can be understood through three main dimensions: regulation and legal framework through Law No. 33 of 2014; facilitation and guidance through halal certification programs and MSME development; and economic diplomacy and international market penetration. The halal industry's contribution to the economy reached USD 42.33 billion in export value with a surplus of USD 31.23 billion in January-October 2023. Synergy between the government and the Indonesian Ulema Council (MUI) through the DSN-MUI fatwa and the application of the concepts of economic justice, community economics, and independent economics strengthens the halal industry ecosystem. The study concluded that comprehensive government policies have shown positive results, although challenges such as global competition and differences in halal standards between countries still require continued attention to strengthen Indonesia's position as a global halal industry hub.